A Prospective Randomized Study between Laparoscopically Assisted Vaginal Hysterectomy and Total Laparoscopic Hysterectomy in a Tertiary Care Hospital - Nessa, Khairun; Dewan, Farhana; Chodhury, Afsana Haque; Chowdhary, Mariha Alam (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Introduction: Hysterectomy is one of the most common gynecological surgeries conducted worldwide. Total Laparoscopic Hysterectomy (TLH) and Laparoscopy Assisted Vaginal hysterectomy (LAVH) have been the mainstays of hysterectomy procedures. When compared with Total Abdominal Hysterectomy (TAH) and LAVH, TLH has been reported to result in shorter durations of procedure, lower blood losses, and shorter hospital stays.Therefore the present study was conducted to compare between operative outcome of LAVH and TLH. Objectives: To compare the surgical outcomes of laparoscopically assisted vaginal hysterectomy, and total laparoscopic hysterectomy in a tertiary care hospital and to determine the challenges of the two methods in terms of cost, logistic supports and need for trained manpower. Study design: A prospective, randomized study was performed at a tertiary care center between January 2019 to January 2020. A total of 50 women indicated to undergo hysterectomy for benign uterine disease were randomly assigned to two groups (25 LAVH, and 25 TLH). The randomization procedure was based on a computer-generated list using serially numbered, opaque, sealed envelopes. A blinded physician randomly assigned each patient to either LAVH (n = 25) or TLH (n = 25). The sequence was concealed until interventions were assigned. Those who performed surgical procedures did not know which patients undergoing surgery had been included in the study. Those assessing the outcomes were blinded to the group assignments. Outcome measures, including operating time, blood loss, rate of complications, level of Hb before and after surgery, need of blood transfusion, consumption of analgesics, and length of hospital stay, were assessed and compared between groups. Results: There were no differences in baseline demographics between the two groups. The TLH group required shorter operating time than the LAVH group. The estimated blood loss was significantly more in the LAVH group than the TLH group. Postoperative hospital stay was slightly more in the LAVH group than the TLH group. Complication rate were similar between the two groups. Three cases in the TLH group needed conversion. Two cases needed conversion to LAVH and 1 case was converted to TAH, all were related to a large lower uterine segment prohibiting visualization during colpotomy. No statistical significant difference was found in regards of postoperative outcome between groups. Conclusions: TLH and LAVH are both safe, feasible procedures with similar surgical outcomes. TLH was associated with shorter operating time and per operative blood loss, whereas LAVH may be preferred in patients with a uterus with a large lower uterine segment. TLH needs more advanced logistic support and more trained manpower in comparison to LAVH. Cost is higher in TLH group than LAVH group. Bangladesh J Obstet Gynaecol, 2021; Vol. 36(1): 18-22